2017
DOI: 10.1186/s12872-017-0623-1
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate home medications among older patients with cardiovascular disease admitted to a cardiology service in USA

Abstract: BackgroundThe use of potentially inappropriate medications (PIMs) may pose more risks than benefits to patients and is a major factor contributing to the likelihood of serious adverse drug reactions and negative health outcomes among older patients.MethodsA retrospective chart review was conducted in a tertiary care center in USA where home medications of the older patients were reviewed and analyzed upon hospital admission over three months, from March till May 2016. Inclusion criteria were age of 65 years an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 23 publications
(11 reference statements)
4
40
2
Order By: Relevance
“…However, 41.6% of the patients were receiving PPIs without a clear indication for it, and this unnecessary use of PPIs is widespread among different countries and not restricted only to HF patients. [ 9,22,23 ] Therefore, the inappropriate consumption of PPIs should be controlled by a proper evaluation of the patients’ medical and medication history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 41.6% of the patients were receiving PPIs without a clear indication for it, and this unnecessary use of PPIs is widespread among different countries and not restricted only to HF patients. [ 9,22,23 ] Therefore, the inappropriate consumption of PPIs should be controlled by a proper evaluation of the patients’ medical and medication history.…”
Section: Discussionmentioning
confidence: 99%
“…This high consumption of benzodiazepine is common between older persons as highlighted by other studies. [ 11,22,23 ] Although there are several alternatives that have been shown to be efficacious in elderly, [ 24 ] patient‐specific assessment is needed to choose the most effective alternative having the lowest risk to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Another commonly prescribed PIM in our study was taken by participants who were diagnosed with the gastroesophageal reflux disease (GERD). A recent study examining the PIM use among older patients with cardiovascular disease also listed the unnecessary use of PPIs common among older adults [ 44 ]. It is important that providers carefully consider the use of PPIs in older adults and monitor their continued use to prevent the drug-drug interactions and side effects, including risk of Clostridium difficile infection, bone loss, and fractures [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Karachi, Pakistan had revealed that at least 1 PIM was prescribed to more than half (64%) of the older population [ 46 ]. It is suggested that many of the PIMs like antihistaminic agents (e.g., diphenhydramine), proton pump inhibitors (e.g., omeprazole and esomeprazole) and analgesics (e.g., aspirin and non-steroidal anti-inflammatory drugs (NSAIDS)) are more frequently used by older people than any other age group [ 47 , 48 , 49 ]. This might be attributable to the reason that old age people mostly suffer from insomnia, heart burn, acid reflex, headache, muscle pain, and joint pain due to multiple co-morbidities and the physicians in developing countries like Pakistan are usually inefficient in diagnosing the underlying cause [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%